AL365181.3 as a novel prognostic biomarker for lung adenocarcinoma - Xiaoying Liu; Jinlong Liu; Yingou Zeng; Di Qiao; Qiang Wang (Scientific Reports)
Abstract As a lncRNA, AL365181.3 is aberrantly expressed in multiple cancer types, including lung adenocarcinoma (LUAD). However, the biological process underlying the ability of AL365181.3 to promote the progression of LUAD is unclear. Here, the pancancer expression level of AL365181.3 was analyzed via the TCGA and GTEx databases, as well as its clinical characteristics and prognostic value. We investigated the biological functions of AL365181.3 in LUAD using various in vitro and in vivo assays. We found that AL365181.3 was significantly more highly expressed in many types of cancer tissues, including LUAD tissues, than in adjacent normal tissues. LUAD patients with high AL365181.3 expression had poor prognoses. Functional enrichment analyses indicated that AL365181.3 is involved in the regulation of metabolism, MAPK signaling and other tumor regulatory signaling pathways. Finally, we found that AL365181.3 knockdown reduced the proliferation, migration and invasion capacity of LUAD cells, and AL365181.3 knockdown resulted in a reduced in vivo tumorigenic capacity of LUAD cells. These findings provide a comprehensive understanding of the role of AL365181.3 in LUAD.